Parametric Study on Environmetal Loads of Hindcast and Measured Full Scale Data - Mayeetae, Zuraida (2011)
The reason of determining the probability of extreme occurrences of wind speed, wave height and current flow is due to the large impact these environmental loads have on the offshore facilities. These occurrences are difficult to predict and may happen once in many years. Several techniques can be used to extract and derive wind, wave and current information from the measured or measured full scale metocean data (PARAS). However, to rely on the measured metocean data alone may not be representative of the accurate sea conditions found locally. This requires correlating the measured metocean data to data derived from Hindcast. This research focuses on the parametric studies of two (2) types of data which are PARAS and hindcast. The hindcast model here is referred to as SEAMOS-South Fine Grid hindcast (SEAFINE) which is derived from a Joint Industry Project (JIP). The objectives of this research are to compare the statistical properties of measured full scale metocean data to the hindcast data through the correlation between winds, waves and currents of measured full scale metocean data and hindcast data in the basins off the coast of Malaysia and finally to validate with statistical certainty on the reliability of the hindcast data. This paper demonstrates some of the previous hindcast studies that have been done in some other regions. The statistical analysis, time series of metocean data and its correlation results are presented here in. Keywords-component; Hindcast, SEAFINE, Time Series, Wind, Wave and Current Correlation